Changes of Age‐related Auricular Cartilage Plasticity and Biomechanical Property in a Rabbit Model. (6th April 2022) - Chen, Lili; Li, Chenlong; He, Aijuan; Tong, Hua; Lu, Xinyu; Yang, Run; Chen, Xin; Wu, Xu; Wang, Xin; Wang, Shuqi; Ma, Jing; Fu, Yaoyao; et al.
Abstract : Objectives: Ear molding is an emerging technique that can correct auricular deformities. Treatment initiation time is the most important prognostic determinant of ear molding. Here, we aimed to examine why auricular cartilage plasticity appeared to diminish with age. Thus, we characterized age‐related changes in the biomechanical, biochemical, and morphological properties of auricular cartilage. Methods: New Zealand rabbits were used as the experimental animal. We examined immature [postnatal 0 day (P0), 5 days (P5), 15 days (P15)], young [2 months (2M)], and mature [6 months (6M)] rabbits. Rabbits' ears were splinted and folded using adhesive fixation strips. Folding duration ranged from 1 day to 5 days to 10 days. Photographs were taken to calculate the retained fold angle. Cartilage morphology and extracellular matrix (ECM) content were examined histologically (using hematoxylin–eosin, Safranin O, elastic Van Gieson, and Masson's trichrome). Water content, DNA content, and cell density were also analyzed. Biomechanical properties were measured using a Nano indenter. Results: Immature ears had smaller angles after strip removal, and the angled deformation lasted a longer time. Cartilage matrix compositions, including glycosaminoglycan (GAG), elastin fiber, and collagen, increased over development. The water content, DNA content, and cell density decreased with age. Young's modulus was significantly higher in mature cartilage. Conclusions: Here, we successfully established an animal model of ear molding and demonstrated that immature cartilage was associated with better plasticity. We also found that the cartilage's biomechanical property increased with the accumulation of ECM. The biomechanical change could underlie age‐related shape plasticity. Level of Evidence: NA Laryngoscope, 133:88–94, 2023